ESTABLISHMENT OF SCHOOL MEDICAL ROOM (UKS) IN ORDER TO IMPROVE THE HEALTH LEVEL OF STUDENTS AND TEACHERS AT MTS AND MAS AL-FATAH KABUPATEN MALANG - Ardhiani, Innas Tiara; Yulindahwati, Asworoningrum (Universitas Airlangga, 2025)
School Medical Room (UKS) have an important role in instilling healthy living behavior and improving students' health through the implementation of the